2005
DOI: 10.1126/science.1110289
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma cruzi Proteome

Abstract: To complement the sequencing of the three kinetoplastid genomes reported in this issue, we have undertaken a whole-organism, proteomic analysis of the four life-cycle stages of Trypanosoma cruzi. Peptides mapping to 2784 proteins in 1168 protein groups from the annotated T. cruzi genome were identified across the four life-cycle stages. Protein products were identified from >1000 genes annotated as "hypothetical" in the sequenced genome, including members of a newly defined gene family annotated as mucin-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

25
345
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 364 publications
(379 citation statements)
references
References 21 publications
25
345
0
9
Order By: Relevance
“…Because its genome is constitutively transcribed into long polycistronic primary transcripts, mRNAs for proteincoding genes must be processed through trans-splicing and polyadenylation reactions. The mRNAs must also interact with different protein factors in a complex posttranscriptional regulatory machinery that determines the levels of their protein product according to the cellular demands of the parasite in each stage of its life cycle.In the same issue that the T. cruzi genome was published (El-Sayed et al 2005a), a study describing its proteome was also reported (Atwood et al 2005). Proteins extracted from whole-cell and subcellular lysates of the four stages of T. cruzi were analysed by mass spectrometry (epimastigotes, metacyclic trypomastigotes, amastigotes and trypomastigotes), which identified 2,784 proteins belonging to the 1,168 protein groups in the annotated T. cruzi genome.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Because its genome is constitutively transcribed into long polycistronic primary transcripts, mRNAs for proteincoding genes must be processed through trans-splicing and polyadenylation reactions. The mRNAs must also interact with different protein factors in a complex posttranscriptional regulatory machinery that determines the levels of their protein product according to the cellular demands of the parasite in each stage of its life cycle.In the same issue that the T. cruzi genome was published (El-Sayed et al 2005a), a study describing its proteome was also reported (Atwood et al 2005). Proteins extracted from whole-cell and subcellular lysates of the four stages of T. cruzi were analysed by mass spectrometry (epimastigotes, metacyclic trypomastigotes, amastigotes and trypomastigotes), which identified 2,784 proteins belonging to the 1,168 protein groups in the annotated T. cruzi genome.…”
mentioning
confidence: 99%
“…Heat-shock proteins (HSP) and proteins involved in vesicular trafficking were also preferentially detected in amastigotes. Furthermore, enzymes involved in antioxidant defence were upregulated during the transformation of epimastigotes into invasive metacyclic trypomastigotes, whereas bloodstream trypomastigotes upregulated the surface expression of several large gene families that are known to be involved in interacting with the mammalian host (Atwood et al 2005).In agreement with this proteomics data, global genomic analyses using microarray technology partially confirmed by real-time polymerase chain reaction (RT-PCR) showed that transcript levels of at least 50% of the T. cruzi genes are significantly regulated during its life cycle (Minning et al 2009). When these authors compared genes that were upregulated in only two stages, they found that 76% of the transcripts were upregulated similarly in stages that exist in the same host (vertebrate host -amastigotes and bloodstream trypomastigotes; insect host -epimastigotes and metacyclic trypomastigotes).…”
mentioning
confidence: 99%
See 3 more Smart Citations